RASIO-RASIO KEUANGAN DALAM MEMPREDIKSI PERUBAHAN LABA (Study Empiris Perusahaan Perbankan di BEI Periode 2009 s/d 2011) (Students' Journal of Accounting and Banking, 2013)
Bank is a place to perform a variety of finance-related transactions. Good or bad of a bank can be seen through the financial ratios contained in published financial statements. Financial report is a report that is used to provide information regarding the financial position and changes in financial position. Financial ratios used in this study is NPM, LDR, DER, and CAR are used to predict changes in earnings. Changes in income is the difference between earnings in the period incurred ynag charge rate to bring about change and determine the profit increase or decrease in profit each year.The population in this study is a banking company listed on the Stock Exchange eriod 2009-2011 totaling 93 companies. This study used a purposive sample of 31 banking companies which are listed on the Stock Exchange only 23 companies to be selected as sample. There are five (4) independent variables that were examined in this study are: NPM, LDR, DER, and the CAR, while the independent variables using the change in earnings. Data collection methods used are literature and documentation. Data analysis techniques using classical assumption test, test multiple linear regression analysis, and hypothesis testing using SPSS tool.The results simultaneously (F test) showed that there are five independent variables jointly affect changes in profitability. In the t test at the 0.05 level indicates that the CAR significant effect on changes in earnings and NPM, LDR, significant negative DER to changes in income.Keywords: changes in earnings and financial ratios (NPM, LDR, DER, dan CAR)